Calculation method for plates with discrete variable thickness under uniform loading or hydrostatic pressure - Aryassov, Gennady; Gornostajev, D.; Penkov, Igor (Zielona Góra: Uniwersytet Zielonogórski)
The article proposes a new analytical method for the calculation of plates with constant and variable rigidity parameters. This method renders it possible to decrease the weight of the plates working under hydrostatic pressure by using variable thicknesses. Firs, a short overview of existing calculation methods and their results are compared. It is shown that all existing methods depend on boundary conditions.
Keywords: plate calculation; deflection; hydrostatic pressure; boundary conditions